Potensi Isolat Bakteri Asam Laktat dari Kombucha Sebagai Antihiperkolesterol Secara In Vitro - Wahyu Adhinugraha, Sandhika; Mayun Permana, I Dewa Gde; Indri Hapsari Arihantana, Ni Made; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i04.p13, 2022)
The objectives of this research were to determine the optimum incubation time of the LAB isolated from kombucha to produce the best bile salt hydrolase activity (BSH) and to better understand its in vitro cholesterol-lowering ability. The experimental design used in this research was Completely Randomized Factorial Design, with 4 isolates of LAB which were L. pentosus MB23; L. pentosus MS21; L. paracasei ssp. paracasei RK41; L. plantarum 1 RB210 and 3 levels of incubation time which were 12, 24, and 36 h were given as the treatments. The 12 combinations were obtained and were done thrice, resulting in 36 experimental units. The data obtained were analyzed using ANOVA and if it showed a significant result, the Duncan Test will be carried out. The results showed that L. plantarum 1 RB210 isolate exhibited its best anti hypercholesterolemic potential at 36 h of incubation with the total LAB of 8.47 log cfu/ml, BSH activity with precipitation diameter of 7.61 mm, and cholesterol-lowering ability of 62.33%.